Wound Healing Problems in the Mouth - Politis, Constantinus; Schoenaers, Joseph; Jacobs, Reinhilde; Agbaje, Jimoh O. (Frontiers in Physiology, 2016)
Wound healing is a primary survival mechanism that is largely taken for granted. The literature includes relatively little information about disturbed wound healing, and there is no acceptable classification describing wound healing process in the oral region. Wound healing comprises a sequence of complex biological processes. All tissues follow an essentially identical pattern to complete the healing process with minimal scar formation. The oral cavity is a remarkable environment in which wound healing occurs in warm oral fluid containing millions of microorganisms. The present review provides a basic overview of the wound healing process and with a discussion of the local and general factors that play roles in achieving efficient would healing. Results of oral cavity wound healing can vary from a clinically healed wound without scar formation and with histologically normal connective tissue under epithelial cells to extreme forms of trismus caused by fibrosis. Many local and general factors affect oral wound healing, and an improved understanding of these factors will help to address issues that lead to poor oral wound healing.